Camylofin 50 mg and Paracetamol 325 mg in patients with acute colicky abdominal pain: a prospective and open-label study - Chandravati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Acute colicky abdominal pain (AP), resulting from the sudden spasm of hollow viscera, is frequently managed with a combination of analgesics and antispasmodics. Camylofin is an anti-spasmodic medication whereas paracetamol is a widely prescribed analgesic and antipyretic for managing mild-to-moderate pain. This study evaluates the effectiveness of a fixed-dose combination (FDC) of camylofin 50 mg and Paracetamol 325 mg in alleviating acute colicky abdominal pain. Methods: In this prospective, single-arm, open-label study, 100 female patients aged 18-65 with acute colicky abdominal pain were administered one tablet thrice daily for 3-5 days of camylofin 50 mg and paracetamol 325 mg daily for 3-5 days. Pain intensity was assessed using the visual analog scale (VAS) at baseline, Day 3 and Day 5. Results: A significant reduction was observed in the mean VAS scores from baseline (77.8) to Day 5 (4.0) (p<0.001). At day 5, 83.0% of patients reported no pain, with minimal adverse events (2% fever and 1% headache with fever). There was a significant change (-27.5) in mean pain intensity VAS score before (77.8) and after (50.2) medication, p<0.001. The percentage change in the mean pain intensity based on VAS score was highest in subjects with urinary AP (97.4%), followed by menstrual AP (94.9%) and unexplained AP (94.5%). Conclusions: The FDC of camylofin 50 mg and Paracetamol 325 mg is significantly effective in managing acute colicky abdominal pain, providing rapid and substantial pain relief with minimal adverse events.